Synthesis, Docking Study, and Biological Evaluation of 2‐Phenylchroman‐4‐one Derivatives as Murine Double Minute 2 (MDM2) Inhibitors. Issue 3 (17th January 2023) - Talebi, Meysam; Boumi, Shahin; Nezamtaheri, Maryam Sadat; Sarmad, Yeganeh; Hosseini, Faezeh Sadat; Delphi, Ladan; Goliaei, Bahram; Amini, Mohsen; Amanlou, Massoud
Abstract: Inhibiting the interaction between the p53 tumor suppressor and its negative regulator murine double minute 2 (MDM2) is a promising therapeutic opportunity in cancer drug research. Herein, we describe the design, synthesis, and in vitro screening of phenyl chroman‐based derivatives 7 a –l as MDM2 inhibitors. Among target compounds, 7 e, 7 h, and 7 j had considerable cytotoxicity activity at concentrations of 50 μM and 100 μM against MCF7 and HCT‐116 cell lines. Designed compounds that demonstrated good toxicity, were selected for enzyme inhibition assay. The most potent MDM2 inhibitor in this series is compound 7 h, which showed a Ki value of 13.66 μM. Moreover, compound 7 h with acceptable safety profiles in normal cells was found the least effective compound against human umbilical vein endothelial cells (HUVECs). In addition, cell cycle analysis was also investigated for representative compound 7 h . Also, the docking study was done to predict the possible interaction between the synthesized compound and both MDM2 and murine double minute x (MDMX) proteins. Interestingly, the docking results were in good agreement with the experimental assay. Abstract : Herein, a series of flavanone‐based derivatives 7 a –l were designed, synthesized and screened as MDM2 inhibitors. Cytotoxicity of all synthesized compounds were evaluated against MCF‐7, HCT‐116, and HUVEC cells line. Compound 7 h, with acceptable safety profiles in HUVEC normal cells, showed a Ki value of 13.66 μM and induced cell growth arrest at the G2/M phase. The docking study showed that selected compounds successfully occupied and interacted with the active site of MDM2 protein.